2013
DOI: 10.1007/s00404-013-2773-4
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and clinico-epidemiological correlates of hepatitis C viral antibodies at an antenatal booking clinic of a tertiary hospital in Nigeria

Abstract: Despite the 3.9 % prevalence, routine screening for hepatitis C virus infection in pregnancy is unjustified. Risk-based screening using locally prevailing risk factors with antenatal monitoring and postpartum treatment of women with hepatitis C antibodies is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
5
9
1
Order By: Relevance
“…As revealed in this study, HCV prevalence has no statistically signi cant association with any of the potential risk factors for HCV even though it was higher among participants with histories of multiple sexual partners and shared needles. This nding is analogous to a previous Nigerian study by Okusanya et al [18] as well as an Ethiopian report by Dabsu and Ejeta [15]. Moreover, since both HIV and HCV or HBV and HCV share common risk factors and mode of transmission, it will be equally important to incorporate information on HCV risk factors into HIV/AIDS and HBV intervention strategies in Nigeria as an alternative.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As revealed in this study, HCV prevalence has no statistically signi cant association with any of the potential risk factors for HCV even though it was higher among participants with histories of multiple sexual partners and shared needles. This nding is analogous to a previous Nigerian study by Okusanya et al [18] as well as an Ethiopian report by Dabsu and Ejeta [15]. Moreover, since both HIV and HCV or HBV and HCV share common risk factors and mode of transmission, it will be equally important to incorporate information on HCV risk factors into HIV/AIDS and HBV intervention strategies in Nigeria as an alternative.…”
Section: Discussionsupporting
confidence: 84%
“…The seroprevalence of anti-HCV antibodies of 1.3% was higher than 0.5% reported previously in Anyigba, Nigeria by Omatola et al [16] and 0.3% reported in India by Parveen et al [17] in an antenatal population in India, but similar to 1.6% reported in a recent Ethiopian study by Dagnew et al [14]. However, this rate was lower than 3.9% reported by Okusanya et al in Irrua, Nigeria [18] as well as ndings of other epidemiological studies that revealed a prevalence of 2 to 4% [16,19,20]. Our ndings were also lower than 8.07% found in a study in Ethiopia [17].…”
Section: Discussionsupporting
confidence: 44%
“…In Nigeria, although hepatitis of other viral origin is widely recognized, [19][20][21] the HEV situation is still largely unknown because incidence of the disease and its etiologic agent are likely underreported. Human HEV genotype 2 infection in Nigeria has been documented 14 and the prevalence of anti-HEV antibodies in humans is~13.4%.…”
Section: Discussionmentioning
confidence: 99%
“…HCV prevalence variation might be explained by the interaction with western countries in Maghreb countries with more open communities than in Libya [58] Eastern Africa 2-2.9% [65] in some reports, and 0% to 2% in others [66] Studies of HCV prevalence are scarce and controversial [65] Southern Africa Has not been well studied [65] Endemicity estimates put the region in the intermediate group [65] Central Africa Prevalence is 4.3% among pregnant women [68][69][70] One of the most heavily infected parts of the world, reaching > 13% in some countries [67]. Cameroon has the highest prevalence (13.8%), followed by Burundi (11.3%) and Gabon (9.2%) [67] Western Africa The prevalence among pregnant women is 3% in Nigeria [71] and 2.2% in Burkina Faso [72] Highly endemic for HCV [71,72] 81]. After delivery, the maternal immune system regains its baseline activity with the resultant decrease in viral load and increase in immune-mediated hepatocyte damage and consequently ALT level [82].…”
Section: Natural History Of Hcv Infection In Infected Pregnant Womenmentioning
confidence: 99%